"Outsiders with Deep Pockets": The Nationalization of Local School Board Elections. (September 2017) - Reckhow, Sarah; Henig, Jeffrey R.; Jacobsen, Rebecca; Alter Litt, Jamie
Recent election cycles have seen growing attention to the role of "outside" money in urban school board elections. Using an original data set of more than 16, 000 contributions covering election cycles from 2008 to 2013 in four school districts (Los Angeles, CA; New Orleans, LA; Denver, CO; Bridgeport, CT), we show how large national donors play a significant role. Our study links two dynamic fields that are rarely studied together: (1) the behavior of wealthy donors in a changing national campaign finance system and (2) the evolving politics of urban education. By examining donor networks, we illuminate the mechanisms behind the nationalization of education politics and national donor involvement in local campaigns. We show that shared affiliations through education organizations are significantly associated with school board campaign contributions.